Business Strategy, Technological Capability, and MSME Performance: The Mediating Role of Competitive Advantage - King Abdul Aziz; Sunu Puguh Hayu Triono (UTSAHA: Journal of Entrepreneurship, 2026)
Micro, small, and medium enterprises operating within free trade zones face intensifying competitive pressures that demand both strategic clarity and technological readiness to sustain business performance. Despite growing scholarly attention to strategy and technology as performance drivers, their simultaneous examination within a mediated structural model remains limited in open industrial zone contexts. This study investigates the influence of business strategy and technological capability on MSME business performance in Batam City, Indonesia, with competitive advantage as a mediating variable. A quantitative explanatory design was employed, with data collected from 350 MSME respondents through a structured Likert-scale questionnaire and analyzed via Partial Least Squares Structural Equation Modeling using SmartPLS 4.1. All seven hypotheses were supported. Both constructs significantly and positively affect competitive advantage and business performance, with technological capability producing the strongest path coefficient in the model, particularly toward competitive advantage. Competitive advantage partially mediates both the strategy-performance and technology-performance relationships. The findings extend the Resource-Based View and Dynamic Capabilities Theory to the MSME free trade zone setting and offer guidance for practitioners and policymakers seeking to support technology-driven competitive development.